2019
DOI: 10.1016/j.heliyon.2019.e02187
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy with transcranial magnetic stimulation and ketamine for treatment-resistant depression: A long-term retrospective review of clinical use

Abstract: Background Both transcranial magnetic stimulation (TMS) and infused ketamine are recognized treatments for patients suffering from major depressive disorder (MDD). A novel therapy named combination TMS with ketamine (CTK) is introduced. This retrospective review examined the safety and clinical benefits of CTK in patients suffering from treatment-resistant depression (TRD) during the routine practice of psychiatry in a private clinic. Methods TRD patients (N = 28) recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 38 publications
1
29
0
Order By: Relevance
“…Retrospective studies including one chart review (28 cases) [ 2 ] and three case reports (with 1–3 cases per article) [ 38 40 ] were identified. A total of four patients received psychopharmacological and psychological therapies, and 28 patients received transcranial magnetic stimulation (TMS), to prolong the antidepressant effects of IV ketamine (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Retrospective studies including one chart review (28 cases) [ 2 ] and three case reports (with 1–3 cases per article) [ 38 40 ] were identified. A total of four patients received psychopharmacological and psychological therapies, and 28 patients received transcranial magnetic stimulation (TMS), to prolong the antidepressant effects of IV ketamine (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of four patients received psychopharmacological and psychological therapies, and 28 patients received transcranial magnetic stimulation (TMS), to prolong the antidepressant effects of IV ketamine (Table 2 ). All patients enrolled in the retrospective studies were diagnosed with TRD and reported suicidal ideation [ 2 , 38 40 ]. Best et al [ 2 ] reported ( n = 28) on the efficacy of combination TMS with ketamine (CTK).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While this would not eliminate variability across participants, it reduces the effects of neurochemical brain state on the primary outcome measure. Combining rTMS and pharmacological treatment is another novel multimodal intervention being developed in adults that could be extended to adolescents ( 219 ). Notably, recent data suggest that combining antidepressant medication with a course of rTMS may in fact have a greater benefit in adolescents than in adults ( 150 ).…”
Section: Limitations Of the Existing Literature And Proposed Resolutionsmentioning
confidence: 99%